Gastrointestinal symptoms in patients hospitalized with COVID-19: Prevalence and outcomes. Issue 25 (24th June 2022) - Song, Jun; Patel, Jay; Khatri, Rishabh; Nadpara, Neil; Malik, Zubair; Parkman, Henry P.
Abstract : Abstract: To characterize outcomes in patients hospitalized with coronavirus disease 2019 (COVID-19) who present with gastrointestinal (GI) symptoms. Clinical outcomes in patients with COVID-19 associated with GI symptoms have been inconsistent in the literature. The study design is a retrospective analysis of patients, age 18 years or older, admitted to the hospital after testing positive for COVID-19. Clinical outcomes included intensive care unit requirements, rates of discharges to home, rates of discharges to outside facilities, and mortality. Seven hundred fifty patients met the inclusion criteria. Three hundred seventy three (49.7%) patients presented with at least one GI symptom and 377 (50.3%) patients presented with solely non-GI symptoms. Patients who presented with at least one GI symptom had significantly lower ICU requirements (17.4% vs 20.2%), higher rates of discharges home (77.2% vs 67.4%), lower rates of discharges to other facilities (16.4% vs 22.8%), and decreased mortality (6.4% vs 9.8%) compared with patients with non-GI symptoms. However, patients who presented with solely GI symptoms had significantly higher ICU requirements (23.8% vs 17.0%), lower rates of discharges home (52.4% vs 78.7%), higher rates of discharges to facilities (28.6% vs 15.6%), and higher mortality (19.0% vs 5.7%) compared with those with mixed GI and non-GI symptoms. Although patients with COVID-19 requiring hospitalization with GI symptoms did better than those without GI symptoms, those with isolated GI symptoms without extra-GI symptoms had worse clinical outcomes. COVID-19 should be considered in patients who present with new onset or worsening diarrhea, nausea, vomiting, and abdominal pain even without pulmonary symptoms.